Analisis Nilai Ekonomi Limbah Rumah Potong Hewan Sapi menjadi Pupuk Organik Cair (Studi Kasus pada RPH Sapi SK Kunak Kota Pontianak) - Jumiati Jumiati; Amalina Aprianti; Yulisa Fitrianingsih (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The increase in population every year has an impact on increasing food demand for beef. The place that plays a role in providing and slaughtering livestock is the slaughterhouse. Pontianak City has one official government-owned cattle slaughterhouse, namely the SK Kunak cattle slaughterhouse. Apart from producing meat, the process also produces by-products, namely waste in the form of rumen, blood, urine, faeces, meat flakes, and fat. However, this slaughterhouse does not have a wastewater treatment plant, so the waste is directly discharged into the environment without further processing. Slaughterhouse waste contains high amounts of organic matter, which can cause air pollution. Cow slaughter waste in the form of rumen and cow blood mainly contains nutrients beneficial for plants, so this waste has economic potential if managed well and appropriately. This research aims to determine the monetary value of slaughterhouse waste in liquid organic fertilizer using a quantitative descriptive approach. The data was analyzed using quantitative descriptive analysis by examining the economic value based on calculating the cost of production (HPP) to determine the selling price of the product. The method used in calculating HPP is variable costing, namely, adding up the production costs of making liquid organic fertilizer in the form of raw material costs, labour, and overhead. The research results show that the production cost of organic fertilizer is IDR. 10,750/litre and the selling price with a 20% profit is Rp. 13,000/litre. As an alternative to liquid fertilizer, the price is lower than the market price, which reaches IDR 75,000/Liter. This liquid organic fertilizer can also be a solution to reduce environmental problems.